REPRESENTASI IDEOLOGI DI BALIK WACANA PEMILU PRESIDEN DAN WAKIL PRESIDEN 2019 DALAM MEDIA KOMPAS: TINJAUAN ANALISIS WACANA KRITIS - Ilyas Zainuddin (Universitas Hasanuddin, 2021)
This study aims to reveal the ideological representation of Kompas news about the 2019 presidential and vice-presidential elections through text forms, discourse practices, and socio-cultural practices. The data collection techniques used are documentation techniques, text observation techniques, and note-taking techniques. The data were analyzed based on Norman Fairclough's critical discourse analysis. The results of this study indicate that the ideology of Kompas media represents the alignment of the presidential candidate pair Joko Widodo-Ma'ruf Amin by looking at the form of the text which is dominated by news that strengthens the position of the presidential candidate pair Joko Widodo-Ma'ruf Amin.